Evaluation of Digital Literacy and Training in Shaping Self-Efficacy towards Teachers' Digital Competence in High Schools - Amilusholihah Amilusholihah; Nani Sutarni; Nugraha Nugraha; Endang Supardi; Susanti Kurniawati (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to evaluate the role of digital literacy and training in shaping teachers' self-efficacy and in contributing to the development of digital competencies among high school teachers. Methodology: A quantitative research design was used, employing a correlational survey. Data were collected from 100 high school teachers in East Java through an online questionnaire. Structural Equation Modeling (SEM) analysis was performed using SmartPLS 4.0 software to evaluate measurement validity, structural paths, and mediation effects. Main Findings: Digital literacy, training, and self-efficacy have a significant, positive influence on teachers' digital competence. Both digital literacy and training also significantly influence teachers' self-efficacy, although the influence is relatively small. In addition, self-efficacy partially mediates the relationship between digital literacy and training in digital competence, underscoring its strategic role in improving teachers' ability to integrate technology into education. Novelty/Originality of this study: This study offers a new perspective by identifying self-efficacy as a psychological bridge between external support (training) and internal competency development. It enriches current knowledge by integrating personal belief systems into the digital competency framework and provides practical implications for designing more effective teacher professional development programs.